DIVERSITY OF MOSS PLANTS (BRYOPHYTA) IN COBAN TALUN, BATU CITY - Royana, Dhita Fitri; Shofi, Fifi Maziyatus; Damayanti, Lisa Kurnia Anggraeni; Zulfa, Naila; Kurniawati, Nika Fitri; Fardhani, Indra; Qomaliyah, Eka Nurul (BIOLINK (Jurnal Biologi Lingkungan Industri Kesehatan), 2025)
Mosses (Bryophyta) are lower plants that lack the vascular tissue, roots, stems and true leaves of higher plants. Lichens can grow in a variety of habitats, including in extreme environments. This study aims to identify the diversity of moss plants in Coban Talun, Batu City, East Java. The sampling technique applied in this study involved dividing the area into 10 plots, with each plot having a size of 3m x 3m. The results obtained from ten plots in the Coban Talun waterfall area showed the presence of 9 species of lichens growing in the location, namely Anoectangium aestivum, Anomodon attenuatus, Campylopus introflexus, Marchantia polymorpha, L. cruciata, Pogonatum inflexum, Andreaea sp., Leucobryum glaucum, and Conocephalum conicum. Moss diversity is strongly influenced by environmental conditions such as temperature, air humidity, and light intensity. At low temperatures (around 25°C) moss diversity is higher than at higher temperatures (around 29°C). At humidity close to 72%, liverwort diversity is more dominant, while at humidity around 62%, leafwort diversity is more dominant.